Traditional and cosmic gods in later Plato and the early Academy - Bartninkas, Vilius (Cambridge classical studies, 2023)
This volume sheds new light on Plato's cosmology in relation to Greek religion by examining the contested distinction between the traditional and cosmic gods, which play a particularly important role in the later dialogues. This theological distinction ultimately collapsed as a result of debates about these ideas in the early Academy.